Die Zigeuner: Reisende in Europa; Roma, Sinti, Manouches, Gitanos, Gypsies, Kalderasch, Vlach und andere - Gronemeyer, Reimer; Rakelmann, Georgia A. (DuMont-Dokumente, 1988)
Literaturverz. S. 220 - 223